Does being overweight impede academic attainment? A systematic review. (September 2014) - Caird, Jennifer; Kavanagh, Josephine; O'Mara-Eves, Alison; Oliver, Kathryn; Oliver, Sandy; Stansfield, Claire; Thomas, James
Objectives: To examine evidence from studies exploring the relationship between childhood obesity and educational attainment. Design: A systematic review of secondary analyses and observational studies published in English after 1997 examining attainment as measured by grade point average or other validated measure, in children aged 6 to16 years, in high-income countries. Methods: Eleven databases from the fields of public health, education and social science were searched, along with 19 specialist registers and catalogues. Hand searching of relevant journals, contacting of experts and citation searching were undertaken. Two reviewers used standardized tools to independently carry out data extraction and assess the quality of included studies. Evidence was synthesized in a narrative summary. Results: Twenty-nine studies were identified for inclusion. Overall, the evidence suggested that higher weight is weakly associated with lower educational attainment among children and young people. Differences between average attainment of overweight and non-overweight children were marginal, with potentially negligible real-world implications for test scores. Limited evidence suggested that little variation in achievement was explained by weight status alone. Almost half the studies found that other factors, such as socioeconomic status, may better explain much of the negative association between obesity and attainment. Conclusion: Theoretical and methodological inconsistencies were evident both within and between many of the studies. As such, the results of the included studies must be interpreted with caution. If the negative association between obesity and attainment is accepted, it still remains doubtful whether obesity is exerting a socially important effect upon educational attainment.